2020
DOI: 10.3390/ma13081849
|View full text |Cite
|
Sign up to set email alerts
|

R-Silsesquioxane-Based Network Polymers by Fluoride Catalyzed Synthesis: An Investigation of Cross-Linker Structure and Its Influence on Porosity

Abstract: Silsesquioxane-based networks are an important class of materials that have many applications where high thermal/oxidative stability and porosity are needed simultaneously. However, there is a great desire to be able to design these materials for specialized applications in environmental remediation and medicine. To do so requires a simple synthesis method to make materials with expanded functionalities. In this article, we explore the synthesis of R-silsesquioxane-based porous networks by fluoride catalysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Our research group has developed highly porous POSS systems with cheap fluoride (F − ) catalysed sol–gel methods from R-alkoxysilanes. 15,16 In that work we found that solvent choice for the sol–gel chemistry could be used to vastly alter the porosity, surface areas, and textures of the synthesized networks. Inspired by that methodology and pure curiosity, we began exploring F − interactions with Q-cages, finding rapid reactivity to form polymeric materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has developed highly porous POSS systems with cheap fluoride (F − ) catalysed sol–gel methods from R-alkoxysilanes. 15,16 In that work we found that solvent choice for the sol–gel chemistry could be used to vastly alter the porosity, surface areas, and textures of the synthesized networks. Inspired by that methodology and pure curiosity, we began exploring F − interactions with Q-cages, finding rapid reactivity to form polymeric materials.…”
mentioning
confidence: 99%
“…From our recent studies, 15,16 catalyst to initiate the reaction. We observed that reactions in all solvent systems evolved large amounts of gas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recently, our research group has focused on understanding fluoride catalysis for the synthesis of porous materials from R-alkoxysilanes. 22,23 Inspired by that methodology, we started examining the possibility of synthesizing porous materials directly from Q8M8 H without the need for additional crosslinkers. By this method, functionalization can be performed before polymerization, which can largely decrease the challenges in making functional porous materials and offer greater application opportunities.…”
mentioning
confidence: 99%
“…From our past research, we found that solvent compatibility tends to have a large influence on fluoride catalyzed polymerization of R-alkoxysilanes, the amount of crosslinker can also drastically affect characteristics of resulting materials. 22,23 In those studies we established ideal solvent conditions for the polymerization processes, and therefore dichloromethane (DCM, Q8M8 H soluble) and acetonitrile (ACN, Q8M8 H insoluble) were determined to be ideal starting points for comparison here (Scheme 1, Fig. S1).…”
mentioning
confidence: 99%